Responsive Human Rights Vulnerability, Ill-treatment and the ECtHR - Heri, Corina (Modern Studies in European Law, 2021)
Who is a vulnerable person in human rights law? This important book assesses the treatment of vulnerability by the European Court of Human Rights, an area that has been surprisingly under explored by European human rights law to date. It explores legal-philosophical understandings of the topic, providing a theoretical framework that can be used when examining the question. Not confining itself to the abstract, however, it provides a bridge from the theoretical to the practical by undertaking a comprehensive examination of the Court's approach under art. 3 ECHR. It also pays particular attention to the concept of human dignity. Well written and compellingly argued, this is an important new book for all scholars of European human rights. The open access edition of this book is available under a CC BY-NC-ND 4.0 licence on www.bloomsburycollections.com. Open access was funded by the Swiss National Science Foundation.